Presentation skills for students - Emden, Joan Van.; Becker, Lucinda. 1963- (New York : Palgrave Macmillan, 2004)
"Presentation Skills for Students is a practical, accessible guide for all students in further or higher education. It discusses speaking effectively in seminars, tutorials and formal presentations and helps with career research including a practical step-by-step guide to a successful job interview. Regular checklists and the friendly down-to-earth style make this an ideal reference tool. The second edition: reflects the changes in technology; includes new material in the job search and job interviews chapter; highlights the hazards of using social networking sites; includes illustrations, which add both clarity and humor"--
Machine generated contents note: Preface -- Personal Development: Speaking to an Audience -- Delivery and Non-verbal Communication and Nerves -- Choosing and Using Visual Aids -- Speaking as Part of Your Course -- Speaking as Part of a Group -- Speaking as a Student Representative -- Speaking at Elections and Meetings -- Job Searches and Job Interviews.
Includes bibliographical references and index.
Keywords: Public speaking; Interpersonal communication